2015
DOI: 10.1007/s11120-015-0179-9
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular organization of photosynthetic complexes in membranes of Roseiflexus castenholzii

Abstract: The photosynthetic membranes of the filamentous anoxygenic phototroph Roseiflexus castenholzii have been studied with electron microscopy, atomic force microscopy, and biochemistry. Electron microscopy of the light-harvesting reaction center complex produced a 3D model that aligns with the solved crystal structure of the RC-LH1 from Thermochromatium tepidum with the H subunit removed. Atomic force microscopy of the whole membranes yielded a picture of the supramolecular organization of the major proteins in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…BChl pigments have been omitted for clarity. The EM models were shrunk 10% to reduce or eliminate the effects caused by detergent and stain on their size [46] , [47] , [48] . …”
Section: Resultsmentioning
confidence: 99%
“…BChl pigments have been omitted for clarity. The EM models were shrunk 10% to reduce or eliminate the effects caused by detergent and stain on their size [46] , [47] , [48] . …”
Section: Resultsmentioning
confidence: 99%
“…The photosynthetic bacterium R. castenholzii has evolved a simple but efficient cyclic ETC to transform solar energy into chemical energy that is different from the linear respiratory chain ( 31 33 ). Our study has revealed the structure of the first photosynthetic ACIII comprising six conserved subunits, in both the air-oxidized and dithionite-reduced states, as well as the nature and position of the cofactors, including six hemes and four iron-sulfur clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced hydroquinone then diffuses from its binding site to the membrane pool through a gap in the LH ring. The hydroquinone is further oxidized by a novel alternative complex (ACIII) found in FAPs that functionally replaces the Cyt bc 1 complex of purple bacteria 33 , and the electron released during this redox reaction is further transferred to a blue copper protein called auracyanin and finally transferred back to the RC via four hemes bound in the Cyt c subunit at the periplasmic side (Fig. 4c ).…”
Section: Discussionmentioning
confidence: 99%
“…Negative stain electron microscopy revealed the core complex from R. castenholzii has a similar size and shape with that of purple bacteria 11 , 13 , 15 , 32 , and has 15 ± 1 LHαβ subunits assembled into a slightly elliptical LH ring, surrounding a tetra-heme cytochrome c bound to the RC 26 . Recently, an electron microscopic 3D reconstruction of the core complex with a resolution of 14.6 Å showed that the LH antenna embraces the RC to form a complete elliptical ring, with the cytochrome subunit protruding to the periplasmic space 33 . However, due to the limited resolution, molecular details about the subunit arrangement and pigment organization are still elusive.…”
Section: Introductionmentioning
confidence: 99%